Reproduction and hibernation strategy of ground-beetles (Coleoptera, Carabidae) along altitudinal gradient: Ground beetles and climate change - Cvetkovska-Gjorgjievska, Aleksandra; Hristovski, Slavčo; Bosheska, Viktorija; Taseska, Angela (Macedonian Journal of Ecology and Environment, 2024)
ABSTRACT Reproduction and hibernation strategies of ground-beetle community along altitudinal gradient on Belasica Mt. were studied. Ground-beetles were systematically collected at 14 different localities by pitfall traps, with monthly dynamics in the period April-November 2010. Four types of reproduction were registered: spring, autumn, spring-autumn and plastic reproduction and both types of hibernation: larva and imago. Dissimilarities in ground beetles’ assemblages between localities were analyzed with cluster analysis. Two groups of localities were registered. First group includes communities inhabiting lower parts, i.e. L1-L4 which were joined on approximately 0.78 % and 0.66% level of similarity (respectively), and the second one groups ground-beetles inhabiting upper altitudinal belt i.e. L7-L14, at 0.54% similarity level of reproduction and hibernation (respectively). Spring breeders as well as ground beetles with plastic reproduction dominated in the localities from upper altitudinal belt. Their abundance as well as the abundance of ground-beetles with adult hibernation was positively correlated with the increasing altitude. These two functional groups of the ground-beetle community are closely interconnected, as confirmed by almost identical dendrographs of the similarity of the carabidocenoses along the gradient. Key words: functional traits, ground-beetles, climate change, mountain АПСТРАКТ Во трудот се прикажани резултатите од анализата на функционалните одлики репродукција и хибернација на тркачите вдолж височински градиент на планината Беласица. Тркачите беа колекционирани од 14 различни локалитети со примена на почвени замки, со месечна динамика во периодот април-ноември 2010 година. Беа регистрирани четири типа на репродукција: пролетна, есенска, пролетно-есенска и пластична, како и два типа презимување: во стадиуми ларва и имаго. Разликите во структурата на карабидоценозите од различните локалитети беа анализирани со примена на кластер анализата. Зависно од типот на репродукција и хибернација беше евидентирано постоење на две групи карабидоценози: првата група вклучува заедници кои живеат во долните делови, т.е. L1-L4 обединети на 0,78% и 0,66% ниво на сличност (соодветно), а втората група се однесува на видовите кои живеат во горниот висински појас, односно L7-L14, со 0,54% сличност ниво на репродукција и хибернација (соодветно). Во локалитетите од горниот висински појас доминираа видовите со пролетна и пластична репродукција. Нивната абундантност како и абундантноста на адултните презимувачи беа во позитивна корелација со зголемувањето на надморската височина. Овие две функционални групи на тркачите се тесно поврзани, што е потврдено со речиси идентичните дендрограми на сличност на карабидоценозите вдолж градиентот. Клучни зборови: функционални одлики, ground-beetles, климатски промени, планина